Increasing Interest in Learning Through Canva-Based Interactive Media at Madrasah Ibtidaiyah Negeri 4 Tebo - putrinurdewi (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This research is motivated by the low interest in learning of grade IV students in the science course at Madrasah Ibtidaiyah Negeri 4 Tebo which can be seen from the lack of attention, interest, feelings of pleasure, and active involvement of students in the learning process, while learning still tends to be centered on teachers and relies on package books as the main learning resource. This research aims to increase students' interest in learning through the application of Canva-based interactive media in learning IPAS. The method used was the Kemmis and McTaggart class action model research which included the stages of planning, implementation of actions, observation, and reflection, with the research subjects of 20 students in grade IV of MIN 4 Tebo. Data collection techniques are carried out through observation, interviews, questionnaires, and documentation, while data analysis uses qualitative and quantitative descriptive. The results showed that the average student learning interest gradually increased from 36.25 in the pre-cycle to 53.75 and 64 in the first cycle, then increased to 74 and 86.25 in the second cycle. Thus, Canva-based interactive media has proven to be effective in increasing students' interest in learning social studies at madrasah ibtidaiyah